2016
DOI: 10.1017/s1041610216002118
|View full text |Cite
|
Sign up to set email alerts
|

Deep microbleeds and periventricular white matter disintegrity are independent predictors of attention/executive dysfunction in non-dementia patients with small vessel disease

Abstract: Arteriosclerotic CMBs and periventricular white matter disintegrity seem to be independent MRI surrogated markers in the early stage of cognitive impairment in SVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…An additional five papers were identified from reference lists. Eight of these 42 papers met inclusion criteria [8,12,2931,3840]. Supplementary Table S2 details these papers and includes key findings from each study.…”
Section: Resultsmentioning
confidence: 99%
“…An additional five papers were identified from reference lists. Eight of these 42 papers met inclusion criteria [8,12,2931,3840]. Supplementary Table S2 details these papers and includes key findings from each study.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 The disruption of brain networks involving the frontal lobe and periventricular white matter was important to determine executive dysfunction and cognitive impairment seen in cSVD, and this may also be the case for CMBs. 31,32…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The disruption of brain networks involving the frontal lobe and periventricular white matter was important to determine executive dysfunction and cognitive impairment seen in cSVD, and this may also be the case for CMBs. 31,32 Another possible pathophysiological mechanism by which CMBs could impair cognition is suggested by studies from animal models, which reported that CMBs induced functional and structural disturbances in the surrounding brain environment: experimentally induced microbleeds disrupted the function of nearby neurons and astrocytes, 33 and promoted an inflammatory response via microglia proliferation and migration, 34 although most of these effects were transient. Alternatively, CMBs might relate to cognition via an indirect effect, through an arteriolar narrowing leading to cerebral hypoperfusion and microischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…22 Previous studies have shown a diversified cognitive profile in patients with VaMCI depending on the characteristics of the sample compared. These studies reported impairment in executive functioning in VaMCI patients compared to normal controls 19 and in attention/executive, memory and visuospatial functioning compared against individuals with small-vessel disease but without cognitive impairment, 53 and decreased impairment in episodic memory (verbal and visual) and executive functioning relative to MCI patients. 54 …”
Section: Discussionmentioning
confidence: 99%